Spin Logic Gates Operated by Protonation and Magnetism in Molecular Combinational Circuits. Issue 6 (25th April 2019) - Zhao, Wenkai; Zou, Dongqing; Sun, Zhaopeng; Xu, Yuqing; Ji, Guomin; Yu, Yongjiang; Yang, Chuanlu
Abstract: The protonation and magnetism effects on the spin transport properties of benzo[b]phenazine (BPE) and bis(o‐phenylenediamine) manganese (IV) complex (Mn‐OPD) molecules in series and in parallel are theoretically investigated using density functional theory (DFT) combined with nonequilibrium Green's function method (NEGF). The spin‐resolved current‐voltage curves show that the magnetic field mainly regulate the spin‐polarized direction of current, and the protonation effect will significantly reduce the magnitude of spin‐polarized current. Moreover, under two orthogonal inputs, the molecular combinational circuits can behave as AND and OR spin logic gates, suggesting the application potential of integrating logic operations for future spin‐based nanoelectronics. In addition, we have observed the Fano resonance phenomenon in the parallel molecular junction, and the Fano resonance feature can be canceled by protonation effect. This work proposes a feasible way to construct a complex single‐molecule spin logic gate device. Abstract : Using density functional theory combined with nonequilibrium Green's function method, the molecular combinational circuits containing benzo[b]phenazine and bis(o‐phenylenediamine) manganese (IV) complex molecules can behave as AND and OR spin logic gates under two orthogonal stimulations (protonation and magnetic field), suggesting the application potential of integrating logic operations for future spin‐based molecular devices.